2013
DOI: 10.1038/nn.3451
|View full text |Cite
|
Sign up to set email alerts
|

Arl13b-regulated cilia activities are essential for polarized radial glial scaffold formation

Abstract: The construction of cerebral cortex begins with the formation of radial glia. Once formed, polarized radial glial cells divide either symmetrically or asymmetrically to balance appropriate production of progenitor cells and neurons. Upon birth, neurons use the processes of radial glia as scaffolding for oriented migration. Radial glia thus provide an instructive structural matrix to coordinate the generation and placement of distinct groups of cortical neurons in the developing cerebral cortex. Here we show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
172
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(180 citation statements)
references
References 47 publications
8
172
0
Order By: Relevance
“…During mouse brain development, neuroepithelial (NEP) cells and RGCs extend a primary cilium into the ventricles (Higginbotham et al, 2013;Fig. S1A).…”
Section: Ventricular Morphogenesis Defects In Ciliary Mutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…During mouse brain development, neuroepithelial (NEP) cells and RGCs extend a primary cilium into the ventricles (Higginbotham et al, 2013;Fig. S1A).…”
Section: Ventricular Morphogenesis Defects In Ciliary Mutantsmentioning
confidence: 99%
“…In the kidney, it also acts as a mechanosensor that detects shear stress, leading to the downregulation of the mTOR pathway necessary for the proper control of cell size (Boehlke et al, 2010;Orhon et al, 2016). The cerebrospinal fluid secreted by the choroid plexus provides diffusible signals that are essential for the early development of RGC Chau et al, 2015;Higginbotham et al, 2013). The apical localization of the primary cilium is thus optimal for detecting chemo-or mechano-sensory signals from the CSF, and thus participates in brain morphogenesis by regulating RGC physiology (Lehtinen and Walsh, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…CSF is then resorbed into the peripheral circulation by arachnoid granulations in venous sinuses of the brain. (Kim et al, 2010;Lehtinen et al, 2011) or the ciliary gene Arl13b (Higginbotham et al, 2013), they share a striking deficiency in IGF signaling receptors and decreased IGF signaling pathway activation on the apical surface of neural stem cells. Recent evidence indicates that IGF1 binding to the IGF1R on primary cilia of radial glial progenitor cells accelerates G 1 -S progression and ciliary resorption by a noncanonical G␀␄ signaling pathway (Yeh et al, 2013).…”
Section: Csf and Distribution Of Instructive Cues In Developmentmentioning
confidence: 99%
“…13,14 More recently, Arl13b signaling in primary cilia has been shown to be crucial for the polarization of radial glial scaffold, an essential step in cerebral cortex formation. 15 To validate the effect of this novel variant in vivo, we took advantage of the phenotypes observed in zebrafish arl13b sco mutants and in Arl13b hnn mouse embryonic fibroblasts (MEFs) and tested the ability of mutated human ARL13B to rescue these phenotypes. We found that wild-type, but not mutant, ARL13B is able to rescue those phenotypes, suggesting that the variant we identified is pathogenic.…”
mentioning
confidence: 99%